Sustentabilidade no Bacharelado em Gastronomia: panorama atual e possibilidades para uma horta pedagógica na Universidade Federal do Ceará - Sei, Alícia (2025)
The Bachelor's Degree in Gastronomy offers comprehensive training, preparing professionals to face complex challenges, such as sustainability in the food system. This study analyzed how an educational garden can be a strategy for teaching sustainability in Gastronomy, focusing on the Bachelor's Degree in Gastronomy at the Federal University of Ceará (UFC). Transformative Learning for Sustainability (TLS) is a concept that refers to educational processes that aim to bring about changes in individuals' perspectives and behaviors in relation to sustainability and, associated with Garden-Based Learning, is an ally in Education for Sustainable Development. Based on the 27 objectives of the TLS, semi-structured interviews were carried out with the course's teachers, with students who interacted with the course's pedagogical garden (G1) and with students who were in their final year (G2), identifying how each group sees the sustainability in the course and how the educational garden can support the teaching of sustainability in Gastronomy. Based on the responses, the TLS objectives were classified considering the TLS status ranking and analyzed to identify what works well and what can be improved in Gastronomy teaching to build new reference frameworks that are focused on sustainability. Furthermore, the Course Pedagogical Projects (CPPs) of the five Bachelor's Degrees in Gastronomy in Brazil were analyzed through content analysis to identify whether/how sustainability is addressed in the courses. It was identified that sustainability is present in all PPCs, varying in frequency and relevance. Although the term is not always used, there is the concept or a context conducive to its approach. The lack of clarity – especially in subject syllabuses – leaves it unclear how teachers should address the topic. In relation to the teachers interviewed, the diversity of formation and performance resulted in heterogeneous responses that enriched the analysis of sustainability in the course, highlighting the absence of a common basis of formation on the topic and the lack of support and institutional structure. The educational garden was identified as a strategy for teaching sustainability in Gastronomy, allowing the cultivation of basic supplies and the use of organic waste from practical classes in composting, integrating sustainability into all stages of the food system. Interviews with G1 indicated that contact with the educational garden contributed to learning about sustainability in Gastronomy, despite the few practical experiences. The students showed interest in further studying the and participating in activities in the garden. Interviews with G2 showed that with adequate stimuli – especially in mandatory content – teaching sustainability in Gastronomy trains critical citizens and agents of change for more sustainable consumption. Students show interest in the topic, engaging even with minimal stimuli. Offering repertoire and experience on sustainability in Gastronomy will enable the construction of new frameworks in the area, based on sustainability, and will train professionals of the future who will build a fairer, healthier and more sustainable food system for everyone